Pengaruh Faktor-Faktor Sumberdaya Manusia terhadap Kinerja Karyawan Pada PT. Wahana Karya Media Banjarmasin - Gisa Marlinawati; Nordin Ideram; Setio Utomo (JURNAL BISNIS DAN PEMBANGUNAN, 2014)
Research purposes to determine and analyze simultaneously the influence of factors of leadership, employee competence, effectiveness, communication, work motivation and marketing strategies on the performance of employees at PT Wahana Karya Media Banjarmasin.The research uses a quantitative approach in this study is intended to facilitate the discussion of analytical, quantitative approach where it is one of the existing approaches in the sociology of science. This approach emphasizes the strict procedures in determining the research variables.Results obtained are the significant influence of the factor of leadership, competence of employees, employee motivation and marketing strategies on the performance of employees at PT Wahana Karya Media Banjarmasin. Not significant for communication effectiveness factor. Keywords: employee performance, human resources